Б) 9m+8m(5-2m)=9m в квадрате - (5m+7)(5m-7)
в) 4x(x-1)-8=(1+2x)(2x-1)-6x
г) -5y+(3y+4)(3y-4)=(4y-3)(3+4y)-7y в квадрате
Пожалуйста помогите решить уравнение!

1

Ответы и объяснения

2013-08-14T10:00:01+00:00
Б) 9m+8m(5-2m)=9m^2-(5m+7)(5m-7)
9m+40m-16m^2=9m^2-(25m^2-35m+35m-49)
9m+40m-16m^2=9m^2-25m^2+49
-16m^2-9m^2+25m^2+9m+40m=49
49m=49
m=1
В) 4х(х-1)-8=(1+2х)(2х-1)-6х
4х2-4х-8=4х2-1-6х
4х=7
х=7/4=1 целая 3/4
Г) -5у+(3у+4)(3у-4)=(4у-3)(3+4у)-7у^2
-5у+(9у^2-12у+12у-16)=(12у+16у^2-9-12у)-7у2
-5у+16у^2-16у^2=7
-5у=7
у=-7/5=- 1 целая 2/5